The Effects of Hypoxia and Anthropogenic Disturbance on the Distribution, Abundance and Recruitment of the Sea Cucumber Holothuria leucospilota at the Mouth of a Subtropical Bay, China - Yu, Zonghe; Zhang, Yingqiu; Zhou, Lei; Sun, Hongyan (Frontiers in Marine Science, 2021)
Despite the commercial importance of the sea cucumber Holothuria leucospilota increasing in recent years, little is known of its spatial distribution and ecology in the South China Sea. We investigate the distribution, abundance, and recruitment of H. leucospilota from 2017 to 2020 at two sites (S1 and S2) in Daya Bay, a typical subtropical bay which is strongly influenced by human activities in the South China Sea. We report hypoxia to drive H. leucospilota from deeper into shallower waters with higher DO concentrations at the mouth of Dapeng Cove in Daya Bay (S1), particularly during summer. Population size at S1 decreased by 90% from 2017 levels, before this area was opened to the public in 2018; recruitment was not observed by August (summer) of 2020. In contrast, in summers of 2017 and 2020, H. leucospilota abundance at S2, a protected open-water area, increased by 84%, and the proportion of small-sized (recently recruited) sea cucumber in the population increased by 20%. Severe summer hypoxia at S1 could negatively influence H. leucospilota spawning and larval settlement, which combined with depletion of broodstock because of fishing pressure and/or hypoxia-induced mortality, could inhibit recruitment. In contrast, higher DO concentrations and abundant broodstock during summer (the breeding season) favoured recruitment of H. leucospilota at S2. Overall, hypoxia and anthropogenic disturbance impede recovery of H. leucospilota at S1, while at the protected S2, larvae may be released to settle in nearby areas. It is imperative to develop a better understanding of the biology, ecology and conservation of tropical sea cucumbers in China.